A damping model for nonlinear dynamic analysis providing uniform damping over a frequency range. (February 2019) - Huang, Yuli; Sturt, Richard; Willford, Michael
Highlights: A model is proposed for intrinsic damping in nonlinear dynamic time-stepping analysis. The model approximates constant energy dissipation over a frequency range of practical interest. The model addresses limitations of previously-available damping algorithms. Abstract: Nonlinear dynamic analysis provides the means for explicitly modeling structural behavior beyond the elastic range, including strength and stiffness deterioration associated with inelasticity and large displacement. Energy-dissipation mechanisms that cannot be explicitly modeled are represented by intrinsic damping. Existing observations suggest that the intrinsic damping of many solid materials is insensitive to frequency. These observations establish one of the primary requirements for a proper damping algorithm. The damping algorithms available in typical commercial nonlinear time-domain finite element codes fall short of this ideal and, in some cases, have other unrealistic effects such as damping of rigid-body modes. This paper presents a practical damping algorithm that offers advantages over existing approaches in its ability to accurately simulate realistic energy dissipation in analyses performed in the time domain. By leveraging filtering protocols, the proposed algorithm realizes frequency-insensitive energy dissipation over a frequency range. It is compatible with all constitutive models and element formulations. It provides orthogonality to rigid-body motion and diminishing damping force for material response beyond the elastic range. It allows different damping levels for individual components. The proposed algorithm is demonstrated to provide a versatile modeling approach for nonlinear dynamic analysis.